Discontinuities in soil strength contribute to destabilization of nutrient‐enriched creeks. Issue 8 (20th August 2018) - Wigand, Cathleen; Watson, Elizabeth B.; Martin, Rose; Johnson, David S.; Warren, R. Scott; Hanson, Alana; Davey, Earl; Johnson, Roxanne; Deegan, Linda
Abstract: In a whole‐ecosystem, nutrient addition experiment in the Plum Island Sound Estuary (Massachusetts), we tested the effects of nitrogen enrichment on the carbon and nitrogen contents, respiration, and strength of marsh soils. We measured soil shear strength within and across vegetation zones. We found significantly higher soil percent organic matter, carbon, and nitrogen in the long‐term enriched marshes and higher soil respiration rates with longer duration of enrichment. The soil strength was similar in magnitude across depths and vegetation zones in the reference creeks, but showed signs of significant nutrient‐mediated alteration in enriched creeks where shear strength at rooting depths of the low marsh–high marsh interface zone was significantly lower than at the sub‐rooting depths or in the creek bank vegetation zone. To more closely examine the soil strength of the rooting (10–30 cm) and sub‐rooting (40–60 cm) depths in the interface and creek bank vegetation zones, we calculated a vertical shear strength differential between these depths. We found significantly lower differentials in shear strength (rooting depth < sub‐rooting depths) in the enriched creeks and in the interface zones. The discontinuities in the vertical and horizontal shear strength across the enriched marshes may contribute to observed fracturing and slumping occurring in the marsh systems. Tide gauge data also showed a pattern of rapid sea level rise for the period of the study, and changes in plant distribution patterns were indicative of increased flooding. Longer exposure times to nutrient‐enriched waters and increased hydraulic energy associated with sea level rise may exacerbate creek bank sloughing. Additional research is needed, however, to better understand the interactions of nutrient enrichment and sea level rise on soil shear strength and stability of tidal salt marshes.